Peningkatan Kinerja Karyawan Melalui Kompetensi Dan Disiplin Kerja Pada PT Bando Indonesia Kota Tangerang - Desrianti, Hemma; Sunarto, Ading (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
Abstrak. This study aims to determine the effect of competence and work discipline on the performance of PT Bando Indonesia employees with method a quantitative approach, the number of samples used is 64 respondents of PT Bando Indonesia employees. The data collection technique used is the questionnaire dissemination technique. The data analysis techniques used were multiple linear regression test, classical assumption test, t test, f test and determination coefficient test with the help of SPSS software program version 25. The results of the study show that the variables of competence (X1) and work discipline (X2) simultaneously have a significant effect on employee performance (Y) at PT Bando Indonesia. The results of the analysis using the determination coefficient are known that the value of the determination coefficient ( obtained is 0.651. This shows that 65.1% of the variation of the Employee Performance (Y) variable can be explained by the Competency (X1) and Work Discipline (X2) variables simultaneously. Meanwhile, the remaining 34.9% is explained by other factors. Where the determination coefficient of 0.651 is included in the strong category, which indicates that the regression model used has better predictive ability on employee performance variables.R^(2 ) Keywords: Competence, Work Discipline, Employee Performance